Juridical Analysis of the 2024 Simultaneous Regional Elections in Realizing Regional Autonomy in Indonesia - Agustiawa, M. Nassir; Samudra, Dian; Hifni, Mohammad (IHSA Institute, 2024)
The 2024 simultaneous regional elections are an important moment in the consolidation of democracy and regional autonomy in Indonesia. The election of regional heads and deputy regional heads directly, generally, freely, secretly, and honestly (Luberjurdil) is expected to be able to produce qualified leaders and be able to realize effective and efficient regional autonomy.The purpose of the research is to juridically analyze the implementation of the 2024 simultaneous regional elections in the context of realizing regional autonomy in Indonesia. This research method uses normative legal research methods with doctrinal and conceptual approaches. Primary data is obtained from legislation, secondary legal materials, and the results of previous research. Secondary data is processed and analyzed by means of interpretation and comparison. The results showed that the organization of the 2024 simultaneous regional elections has a strong legal basis, namely Law Number 23 of 2014 concerning Regional Government. The implementation of the 2024 simultaneous regional elections is an important step in realizing regional autonomy in Indonesia